A new record after a century and description of the female of Plectrogonodesmus gounellei (Brölemann 1902) (Polydesmida: Chelodesmidae). (2nd January 2019) - Bouzan, Rodrigo Salvador; Iniesta, Luiz Felipe Moretti; De Souza, Cláudio Augusto Ribeiro; Brescovit, Antonio Domingos
ABSTRACT: The monotypic genus Plectrogonodesmus Hoffman, 2012 is revisited. Currently, the genus comprises only the species Plectrogonodesmus gounellei Brölemann, 1902, described based on a single male specimen. In this work, we describe the female for the first time, and complement the description of the males. Furthermore, a revised diagnosis for the genus and a distribution map are provided.